2009
DOI: 10.7249/mg889
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Adequacy and Efficiency in California: Issues, Policy Options, and Recommendations

Abstract: This document and trademark(s) contained herein are protected by law as indicated in a notice appearing later in this work. This electronic representation of RAND intellectual property is provided for non-commercial use only. Unauthorized posting of RAND PDFs to a non-RAND Web site is prohibited. RAND PDFs are protected under copyright law. Permission is required from RAND to reproduce, or reuse in another form, any of our research documents for commercial use. For information on reprint and linking permission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In making the choice to adopt a targeted versus universal program, there are several considerations for policymakers and the public. Table 4.4 summarizes some of the most-salient criteria and how they vary across the two approaches (Wolfe and Scrivner, 2003;Barnett, Brown, and Shore, 2004;Karoly, 2009). A targeted program would be favored in the case of the first two criteria-cost and displacement.…”
Section: Targeted Versus Universal Programsmentioning
confidence: 99%
See 3 more Smart Citations
“…In making the choice to adopt a targeted versus universal program, there are several considerations for policymakers and the public. Table 4.4 summarizes some of the most-salient criteria and how they vary across the two approaches (Wolfe and Scrivner, 2003;Barnett, Brown, and Shore, 2004;Karoly, 2009). A targeted program would be favored in the case of the first two criteria-cost and displacement.…”
Section: Targeted Versus Universal Programsmentioning
confidence: 99%
“…On the one hand, a targeted program would be expected to generate a higher per-child economic return (e.g., benefit-cost ratio). However, the total aggregate returns might be higher with a universal program because the cumulative benefits aggregated across all children could outweigh the higher per-child benefit summed over a smaller group of children (see Karoly, 2009, for an illustration).…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…The ECERS-R Manual on Indicator 7.1 recommended initiating social conversations and suggested that meal times is a superb time to do this to improve relationships, find out about the children's lives, and talk about concepts. In the RAND Corporation follow-up report of the original research, it was noted that a quality gap existed with respect to how teachers encourage language development and higher-level thinking skills that are necessary for school readiness (Karoly, 2009). As Han et.…”
Section: Commissioned By the California Governor's Committee On Educamentioning
confidence: 99%